2013
DOI: 10.3109/10715762.2013.821200
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK: A dual role in hepatocyte proliferation through reactive oxygen species

Abstract: p38 MAPKs are important mediators of signal transduction that respond to a wide range of extracellular stressors such as UV radiation, osmotic shock, hypoxia, pro-inflammatory cytokines, and oxidative stress. The most abundant family member is p38α, which helps to couple cell proliferation and growth in response to certain damaging stimuli. In fact, increased proliferation and impaired differentiation are hallmarks of p38α-deficient cells. It has been reported that reactive oxygen species (ROS) play a critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 155 publications
2
69
0
3
Order By: Relevance
“…Importantly, reconstitution of p38 activity by ectopic expression of constitutively active MKK3(EE) in Ubc13-deficient BCa cells restores their metastatic potential. Involvement of p38 MAPK signaling in cancer development, progression, and metastasis has been demonstrated previously (45)(46)(47)(48). The p38 MAPK was suggested to overcome ERK signaling to promote survival of dormant cancer cells through activation of the unfolded protein response (49)(50)(51), as well as various steps in the process of invasion and metastasis (20).…”
Section: Discussionmentioning
confidence: 81%
“…Importantly, reconstitution of p38 activity by ectopic expression of constitutively active MKK3(EE) in Ubc13-deficient BCa cells restores their metastatic potential. Involvement of p38 MAPK signaling in cancer development, progression, and metastasis has been demonstrated previously (45)(46)(47)(48). The p38 MAPK was suggested to overcome ERK signaling to promote survival of dormant cancer cells through activation of the unfolded protein response (49)(50)(51), as well as various steps in the process of invasion and metastasis (20).…”
Section: Discussionmentioning
confidence: 81%
“…As demonstrated by the ABTS assay (Figure 4b), 100 μg/ml RPE exhibited over 90% ABTS radical scavenging activity; this was comparable to that of 10 μg/ml vitamin C (Figure 4a). As we described in the introduction section, aberrant ROS production can accelerate DNA damage and activate inflammatory signaling pathways (Chen et al., 2006; Tormos et al., 2013). Therefore, we hypothesized that suppression of MAPK signaling pathway is mediated by antioxidant activities of RPE.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that ROS activates inflammatory signaling pathways (Chen et al., 2006; Tormos, Talens‐Visconti, Nebreda, & Sastre, 2013). We also found that N ‐acetyl cysteine (NAC, a ROS scavenger) drastically inhibited sUV‐induced matrix metalloprotein‐1 (MMP‐1) expression (data not shown) and siRNA of p47 phox , a subunit of NADPH oxidase (NOX); as a result, reduction of EGFR transactivation in NADPH oxidase was observed (Chen et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…55 The ultimate effect of p38 MAPK activation depends on the type of stimulus in a cell-type-specific manner. [56][57][58] To further explore the role of p38 activation in response to VX680 treatment, we treated cells with BIRB796. BIRB796 is a novel p38 MAPK inhibitor that inhibits all p38 MAPK isoforms in vitro and vivo.…”
Section: Discussionmentioning
confidence: 99%